Label-free assessment of replicative senescence in mesenchymal stem cells by Raman microspectroscopy - Bai, Hua (Biomed Opt Express, 2015)
Here, Raman microspectroscopy was employed to assess replicative senescence of mesenchymal stem cells (MSC). A regular spectral change related to the cell senescence was found in the ratio of two peaks at 1157 cm(−1) and 1174 cm(−1), which are assigned to C-C, C-N stretching vibrations in proteins and C-H bending vibrations in tyrosine and phenylalanine, respectively. With the cell aging, the ratio I(1157) / I(1174) exhibited a monotonic decline and showed small standard deviations, so that it can statistically distinguish between cells having slight changes in terms of aging. We propose that I(1157) / I(1174) can act as a characteristic spectral signature for label-free assessment of MSC senescence.